An Investigation of Thai Students’ English Language Problems and Their Learning Strategies at English Study Program of Teacher Training and Education Faculty of Riau Islamic University - Wahyuni, Sri; Ilyas, Muhammad (J-SHMIC : Journal of English for Academic, 2016)
The purpose of this study was to investigate the English language problems and learning strategies. The study employed a survey design which involved administering questionnaires of rating scales, using Rubin, J., & Thompson, I. (1994) and Rebecca Oxford (1990) Strategy Inventory for Language Learning (SILL), to measure English language problems and language learning strategies from 10 Thai students  of English Study Program of Teacher Training and Education Faculty at Riau Islamic University. The result of this study revealed that the most serious problem of Thai students in English Language Learning is listening and writing skills while reading skill is the least problem. Another big problem involved being unable to write an essay within limited time and always have a listening problem. Beside, the problem least mentioned is unable to understand classroom lectures in English. All Participant reported a high frequency use of strategy on the SILL. The participants reported using social strategies most frequently and metacognitive strategies least frequently but in medium range. The most frequently used strategies involved asking lecture or classmate for helping. Not trying guess if they do not fully understand what is being said was the least frequently used.